2010
DOI: 10.1111/j.1365-294x.2010.04795.x
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight-related suboptimal conditions can accentuate the altered gravity response of Drosophila transcriptome

Abstract: Genome-wide transcriptional profiling shows that reducing gravity levels during Drosophila metamorphosis in the International Space Station (ISS) causes important alterations in gene expression: a large set of differentially expressed genes (DEGs) are observed compared to 1g controls. However, the preparation procedures for spaceflight and the nonideal environmental conditions on board the ISS subject the organisms to additional environmental stresses that demonstrably affect gene expression. Simulated microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 32 publications
(28 reference statements)
10
43
0
Order By: Relevance
“…Interestingly, the internal controls used in the ground-based facility experiments described here also reveal some effects on the gene expression profile, possibly due to magnetic stresses in levitation or subtle mechanical forces in the RPM such as vibrations, other than those which compensate gravity. Nevertheless, these results, in combination with earlier experiments in real or simulated microgravity conditions [7,29], indicate that the transcriptome is finely tuned to Earth´s gravity and that the synergic effects exerted by microgravity and environmental suboptimal conditions may be explained by this "out of tune" state of the transcriptome in microgravity.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, the internal controls used in the ground-based facility experiments described here also reveal some effects on the gene expression profile, possibly due to magnetic stresses in levitation or subtle mechanical forces in the RPM such as vibrations, other than those which compensate gravity. Nevertheless, these results, in combination with earlier experiments in real or simulated microgravity conditions [7,29], indicate that the transcriptome is finely tuned to Earth´s gravity and that the synergic effects exerted by microgravity and environmental suboptimal conditions may be explained by this "out of tune" state of the transcriptome in microgravity.…”
Section: Discussionsupporting
confidence: 51%
“…All samples were processed using Affymetrix Drosophila (Drosophila Genome2) chips covering near the whole fly coding genome. A validation of this approach, including qRT-PCR has been already published by our team [7].…”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main conclusions from the gene expression analysis are that the exposure of the samples to the strong magnetic field, with or without a field-gradient, caused significant changes in the expression of immune, stress, and temperature response genes (several heat shock proteins, for instance, appear affected). It is notable that experiments of different durations activated or repressed different genes, although in similar GO groups (Figure 3), and also that these GO groups are similar to the ones found in real microgravity conditions in space [21,23]. Our results indicate that the vertical diamagnetic force (that levitated the flies in the 0 g * tube and enhanced the net effective weight of the flies in the 2 g * tube) had less of an influence on the transcription profile than other effects of the strong magnetic field, which was present in all three tubes (11.5 T in 0 g * and 2 g *, and 16.5 T in 1 g *).…”
Section: Discussionmentioning
confidence: 65%
“…The genome-wide transcriptional profile showed that the presence of the reduced gravity level during Drosophila metamorphosis in the experiment at the ISS resulted in changes in the gene expression profile, primarily in stress reactions [22], which was confirmed in the experiments conducted using the random position machine [23]. The products of these differentially expressed genes are involved in respiration, development, morphogenesis processes, and the formation of the stress response [24].…”
Section: Discussionmentioning
confidence: 97%